In this moment [large type] : a novel - Kingsbury, Karen (Kingsbury, Karen. Baxter family, 2017)
"When he receives national attention and criticism for starting an after-school Bible study and prayer program, Wendell Quinn chooses attorney Luke Baxter to help him fight the battle." --